ChemInform Abstract: 2‐Pyridylmethyl Ether: A Readily Removable and Efficient Directing Group for Amino Acid Ligand Accelerated ortho‐C—H Olefination of Phenols. Issue 18 (11th April 2013) - Cong, Xuefeng; You, Jingsong; Gao, Ge; Lan, Jingbo
Abstract It is demonstrated that 2‐pyridylmethyl ether can serve as an efficient directing group for amino acid accelerated ortho‐C—H olefination of phenols via a seven‐membered cyclopalladated intermediate.